Field notes contributed by Peter C. Petersen, spring 1980 - Petersen, Peter C.et al (1980)
List of birds and locations contributed by Peter C. Petersen with observers Mary Lou Petersen, Walter Zuurdeeg, Clark Scott and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed